Prevalence of Work-Related Musculoskeletal Disorders among Dental Workers in Enugu Metropolis, Nigeria - Canice C. Anyachukwu; Faith N. Ezugwu; Stephen S. Ede; Ogochukwu K. Onyeso; Charles I. Ezema; Chisom F. Ede (International Journal of Medicine and Health Development)
Background: Work-related musculoskeletal disorders (WRMSD) are the main occupational health hazard among several clinicians, but its prevalence among dental workers in Nigeria has not been well-studied. Objective: This study evaluated the pattern and prevalence of WRMSDs among dental workers in the Enugu metropolis, Nigeria. Materials and Methods: Six hospitals with dental clinics participated in this cross-sectional survey in the Enugu metropolis. One-hundred and fifty (150) standardized musculoskeletal symptom (Nordic) questionnaires were adopted and distributed, of which 141 were returned. The questionnaire elicited data on demographic characteristics and carrier profiles, ergonomics, and the body parts involved in the occupational activities. Results: The results indicated that 83% of the respondents sustained musculoskeletal injury more than once. Bending (66%) and performing repetitive tasks (58.2%) were the most performed risk activities. The lower back (66%) was the most affected body part, followed by the upper back (58.9%), neck (51%), shoulder (47.5%), and hip (46.1%). The most common preventive measures taken by individuals were resting (57%) and avoiding lifting (53.2%). Conclusion: There is a high prevalence of WRMSD among dental workers, with potential to having negative effect on their work habits, and reduced productivity.